Educa????o n??o formal para l??deres sindicais empresariais: avalia????o do Projeto Avan??a Sindicato - Mello, Mait?? Sarmet Moreira Smiderle (2017)
How can empowerment actions help improve employers' union leaders performance? Employer??s unions have an important role of representing industrial enterprises, but their leaders, most of the times, are entrepreneurs who take over their entities without sufficient management training. Identifying this need, the Brazilian National Confederation of Industry (CNI), through its Associative Development Program (PDA), started to structure educational actions focused on this public and offered through a Project called ???Union advance???. This case study involved documentary analysis and semi-structured interviews with Union presidents, state and national program managers. Results indicate that Unions have improved their performance in several areas, such as communication, advocacy, collective bargaining and service delivery. In this sense, it is already possible to notice that most leaders have been awakening for the need of a professional management within their corporate representation entities. The interviews conducted in this study confirmed the relevance of capacity building initiatives delivered by the Project ???Union advance??? to make possible vital changes in the profile and performance of the union leaders in the last years.